Pemberantasan Buta Huruf Al-Qur’an dengan Metode Iqra’ di Desa Pulau Gambar Kabupaten Serdang Bedagai - Husna Sari Siregar; lfian Arbie; Riska Hadiyati; Triska Andini (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Factors that cause children to not be able to read the Qur'an properly and correctly in Pulau Gambar Village, including the lack of parental interest in teaching children to read the Qur'an, parents' incomprehension of reading the Qur'an, the lack of young people as teachers of the Koran in the village, technological sophistication, lack of government attention and the application of less effective learning methods. The method used is the Iqra 'method, which is a method of reading the Qur'an which prioritizes directly on reading practice. The Iqra 'method has three stages, namely preparation, implementation and evaluation. At the preparation stage, all children already have iqra'', then in its implementation it must be in accordance with the provisions set out in the iqra' book, namely the teaching instructions at the beginning of each volume whose implementation is carried out by means of CBSA. After that, it was evaluated to find out the improvement in children's reading. Eradication of illiteracy in the Qur'an with the iqra' method in Pulau Gambar Village, Serdang Bedagai Regency has been said to be successful where in the process, the iqra' method can improve learning in introducing hijaiyah letters to children so that they can read the Qur'an well and fluently. Keywords: Illiteracy, Al-Qur'an, Iqra' Method